2018
DOI: 10.1055/s-0038-1642603
|View full text |Cite
|
Sign up to set email alerts
|

Association between Hormonal Contraception and Injuries Induced by Human Papillomavirus in the Uterine Cervix

Abstract: Objective To evaluate the association between hormonal contraception and the appearance of human papillomavirus HPV-induced lesions in the uterine cervix of patients assisted at a school outpatient clinic -ObGyn outpatient service of the Universidade do Sul de Santa Catarina. Methods A case-control study, with women in fertile age, performed between 2012 and 2015. A total of 101 patients with cervical lesions secondary to HPV were included in the case group, and 101 patients with normal oncotic colpocytology, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 36 publications
(66 reference statements)
3
10
0
Order By: Relevance
“…Regarding the use of OC, the findings confirm previous studies (5,18) . One of these showed that the intake of contraceptives, regardless of the type, was a risk factor for cervical alterations, and, when associated with the number of sexual partners, made the outcome more likely, corroborating the characteristics of the latter as an independent factor for cervical changes in this research.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Regarding the use of OC, the findings confirm previous studies (5,18) . One of these showed that the intake of contraceptives, regardless of the type, was a risk factor for cervical alterations, and, when associated with the number of sexual partners, made the outcome more likely, corroborating the characteristics of the latter as an independent factor for cervical changes in this research.…”
Section: Discussionsupporting
confidence: 89%
“…Other factors contribute for the natural history of the disease. These include the immunological response of the host, viral genetic profiles, the early beginning of sexual activities, multiple partners, a previous history of Sexually Transmitted Infections (STIs), the use of oral contraceptives (OC), smoking, nutritional deficiencies, low socioeconomic level of the host (5) , all of which are potential axes for interventions.…”
Section: Introductionmentioning
confidence: 99%
“…There have been differing opinions on the use of hormonal contraceptives and cervical HPV persistence where some authors reported association (13,24) while some others reported no association (25,26). In this study, use of hormonal contraceptive was associated with HPV clearance instead of persistence though this should be interpreted with caution as the duration of hormonal contraceptive use and the type of contraceptives were not specified.…”
Section: Discussionmentioning
confidence: 60%
“…HPV-positive women raise some concerns about choosing their contraceptive method. Although, to conclude causality between COCs and HPV lesions, more studies are needed [ 16 ], particular attention should be given to discuss contraception methods with HPV-positive women.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, long-term use of birth control pills increases cervical cancer risk, importantly for women with persistent HPV infection. However, users of combined oral contraceptives (COCs) have a decrease in immune cells providing a favorable environment for the appearance of HPV lesions [ 16 ]. Women may worry about these issues but the literature is limited.…”
Section: Introductionmentioning
confidence: 99%